Mitochondria-targeted reactive oxygen species blockor SS-31 blocks hepatic stellate cell activation and alleviates hepatic fibrosis by regulating NLRP3 inflammasomes: SS-31 in hepatic fibrosis - Liu, Li; Wei, YingFeng; Xie, NingSheng; Cai, Hong; Lin, Ye (Cellular and Molecular Biology, 2024)
This study aimed to elucidate the effect of mitochondria-targeted reactive oxygen species (ROS) blockor SS-31 on hepatic stellate cells (HSC) activation during liver fibrosis. TGF-β1 was employed to induce HSC activation, while MitoSOX Red was utilized to assess the presence of mitochondrial ROS. The mitochondrial membrane potential (MMP) was measured using the JC-1 probe, and the ATP level was determined using a specific kit. The proliferation of HSCs was assessed using CCK-8 and colony formation assays, whereas flow cytometry was employed to detect HSC apoptosis. Fibrotic markers (COL1A1 and α-SMA) and NLRP3 inflammasome components (NLRP3, caspase-1, and ASC) were analyzed via Western blotting. Liver fibrosis was induced in mice using CCl4, and subsequently, histopathological changes were observed through HE staining and Masson staining. In TGF-β1-activated HSCs, mitochondrial ROS expression increased, MMP and ATP content decreased, indicating mitochondrial damage. After TGF-β1 induction, HSC proliferation increased, apoptosis decreased, and COL1A1, α-SMA, and NLRP3 inflammasome protein expression increased. After SS-31 treatment, mitochondrial ROS expression decreased, MMP recovered, ATP level increased, HSC proliferation decreased, apoptosis increased, and the expressions of COL1A1, α-SMA, and NLRP3 inflammasome decreased. NLRP3 blockor MCC950 treatment blocked HSC activation. CCL4-induced liver fibrosis mice had inflammatory cell infiltration and significant collagen fiber deposition in the liver. After SS-31 treatment, liver inflammation and collagen deposition were significantly reduced. SS-31, as a mitochondria-targeted ROS blockor, can block HSC activation by regulating the NLRP3 inflammasome, thereby alleviating liver fibrosis.